Estimation of body composition in Chinese and British men by ultrasonographic assessment of segmental adipose tissue volume. Issue 1 (March 1994) - Eston, R; Evans, R; Fu, F
Abstract : It has been shown that ultrasonographic measurements can be used to predict body composition in adults. The purpose of this study was to assess the relationship between ultrasonograph and caliper (SKF) measurements of subcutaneous adipose tissue thickness in athletic Caucasian (English, E) and Asian (Chinese, C) men against estimates of body composition determined from hydrodensitometry (HYD). The usefulness of a proposed ultrasonographic method of estimating lean and fat proportions in the upper and lower limbs was also evaluated as a potential method of predicting body composition. Ultrasonography (US) was used to measure adipose and skin thickness at the following sites: biceps, triceps, subscapular, suprailiac, abdominal, pectoral, thigh and calf. Caliper measurements were also made at the above sites. Subcutaneous fat thickness and segmental radius were measured directly from the display screen of the ultrasonic scanner (Aloka 500 SD). By applying the geometry of a cone, the proximal and distal radii of the upper arm and upper leg were used to calculate the proportionate volumes of adipose tissue. The best correlations for US and SKF were obtained at the quadriceps, subscapular and pectoral sites for E (r = 0.96, 0.93 and 0.90, respectively) and at the quadriceps, calf and abdominal sites for C (r = 0.90, 0.81 and 0.75, respectively). The best ultrasonographic predictor of the percentage fat in both groups was the percentage adipose tissue volume in the upper leg (r = 0.83 and 0.79 for C and E, respectively). Stepwise multiple regression analysis indicated that the prediction of percentage fat was improved by the addition of the ultrasonographic abdomen measurement in both groups: Chinese sample: %fat = %fat(leg) (0.491) + US abdomen (0.337) + 0.95 ( R = 0.89, s.e.e. = 1.9%); English sample: %fat = %fat(leg) (0.435) + US abdomen (0.230) - 0.765 ( R = 0.80, s.e.e. = 3.6%). It is concluded that ultrasonographic measurements of subcutaneous adipose tissue and volumetric assessment of percentage adipose tissue in the thigh are useful estimates of body composition in athletic English and Chinese males.